POOR PROGRESS STUDENTS IN LEARNING MATHEMATICS AS SOCIAL AND PSYCHOLOGICAL-PEDAGOGICAL PROBLEM - Tatochenko, В.І.; Shypko, А.Л. (Journal of Information Technologies in Education (ITE), 2016)
The article is devoted to theoretical substantiation of modern methodical system of Mathematics teaching of poor progressing secondary school pupils. A systematic approach to the study of psycho-pedagogical determinants of poor progress of pupils in math was implemented. The dynamic of interfunctional relationship of structure of educational and informative sphere of poor progressing pupils in mathematics was disclosed and scientific understanding of this process was expanded. The introduction in the educational process of didactic methodical and psychologically balanced methodical control system and correction of poor progressing students’ in Maths improves quality indicators of their permanent knowledge and skills. It allows you to discover the fullness, depth and durability of learning at different stages and levels of education, it contributes to correction, management and partly self-management learning process of poor progressing students in Mathematics, excites them to an active mental activity promotes the development of a conscious attitude to their systematic academic work. The essence of “poor progress” phenomena is observed as well as “educational retardation” of school students during teaching mathematics. Target orientation, the resource potential of the real educational process of poor progressing pupils in Mathematics are determined. Contradictions are singled out and pedagogical conditions of results control of learning outcomes of comprehensive school pupils are proved. An attempt to consider the academic failure of schoolchildren in Mathematics in connection with the main categories of didactics – the content and the learning process was made. Certain shortcomings of teaching and learning activities of students in the study of Mathematics are highlighted as poor progressing elements and gaps. The process and content, enriched with the use of NIT, ensuring the formation of key competencies of lagging behind and underachieving in math student as social,communicative, informative, cognitive.